Positivity of HIV, hepatitis B and hepatitis C in patients enrolled in a confidential self-exclusion system of blood donation: a cross-sectional analytical study - Kasraian, Leila; Tavasoli, Alireza (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: Selection of healthy blood donors is essential to ensure blood safety. A confidential self-exclusion (CSE) system was designed so that high-risk donors could confidentially exclude their blood from use in transfusions. This study aimed to compare the demographic characteristics and the results from human immunodeficiency virus (HIV), hepatitis B surface (HBS) and hepatitis C virus (HCV) screening tests on donors who opted to get into and out of CSE. DESIGN AND SETTING: Analytical cross-sectional study on all volunteer donors at Shiraz Blood Transfusion Organization from March 21, 2006, to March 21, 2008. METHODS: The results from the abovementioned tests were compared between donors who opted into and out of CSE. RESULTS: 100,148 donors in 2006 and 104,271 in 2007 gave blood. Among these donors, respectively, 829 (0.82%) and 592 (0.57%) opted for the CSE. The prevalence of HIV antibodies, HBS antigens and HCV antibodies in CSE donors was significantly higher than in donors who did not choose CSE (p < 0.05). The prevalence of at least one of these three infections among CSE donors was 3.12% in 2006 and 3.04% in 2007, and was significantly higher than the prevalence among non-CSE donors (0.58% and 0.57%, respectively). CONCLUSION: Because of the higher prevalence of HBS, HCV and HIV positivity in blood donors who chose the CSE option, offering CSE to blood donors could be a potentially useful method for improving blood safety, since it could increase the detection of infected blood during the window period.